Composition and Activity of the Board of Directors: Impact on ESG Performance in Nepalese Banking System - Paudel, Suman; Kasaudhan, Sushmita (Nepalese Journal of Finance, 2024)
This study examines the composition and activity of the board of directors on ESG performance in Nepalese banking system. ESG performance is selected as the dependent variable. Similarly, board size, independent directors, audit committee, board meetings, women in the board and government ownership are selected as the independent variables. This study is based on secondary data of 15 banks with 105 observations for the study period from 2015/16 to 2021/22. To achieve the purpose of the study, structured questionnaire is prepared. Secondary data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the timeliness of financial reporting in Nepalese banks.The study revealed that board size has a positive impact on ESG performance. It means that increase in board size leads to increase in ESG performance. Likewise, independent director has a positive impact on ESG performance. It shows that higher the independent director, higher would be the ESG performance. Moreover, this study showed board meeting has a positive impact on ESG performance. It means that increase in board meeting leads to increase in ESG performance. Further, audit committee has a positive impact on ESG performance. It shows that higher the audit committee, higher would be the ESG performance. Likewise, government ownership has a negative impact on ESG performance. It indicates that increase in government ownership leads to decrease in ESG. Similarly, women in the board have a positive impact on ESG performance. It indicates that increase in women in the board leads to increase in ESG performance.